Effectiveness of mechanical brushing with different denture cleansing agents in reducing in vitro Candida albicans biofilm viability - Pellizzaro, Delise [UNESP]; Polyzois, Gregory; Machado, Ana Lucia [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Sanitá, Paula Volpato [UNESP]; Vergani, Carlos Eduardo [UNESP] (FapUNIFESP (SciELO), 2012)
The adhesion of Candida albicans to surfaces is the prerequisite for occurrence of denture stomatitis, a common disease diagnosed among denture wearers. A routine of denture cleansing is essential to prevent biofilm formation and the onset of this infection. The aim of this study was to investigate the effectiveness of combining brushing and cleansing agents in killing C. albicans biofilm. Disks of acrylic resin were made, sterilized, and inoculated with C. albicans (107 cfu/mL). After incubation (37°C/48 h), specimens were randomly assigned to 10 experimental groups (n=9): 5 subjected to brushing with distilled water or cleansing agents - dentifrice slurry, 2% chlorhexidine gluconate (CHX), 1% sodium hypochlorite (NaOCl), and Polident fresh cleanse® (combined method) - and 4 exposed to the cleansing agents without brushing (immersion). Non-cleansed specimens were used as positive controls. The viability of cells was evaluated by XTT reduction method. Results were analyzed by Mann-Whitney and Kruskal-Wallis tests (α=0.05). The combined method was significantly more effective (p<0.0001) in reducing biofilm viability than the immersion. Brushing with CHX and NaOCl resulted in 100% removal of the biofilm. Immersion in the agents reduced significantly (p<0.0001) the biofilm viability, with CHX being the most effective (p<0.0001). The use of the combined method of brushing with cleansing agents is an effective method to reduce C. albicans biofilm, being CHX and NaOCl the most effective solutions.
Keywords: Acrylic resins; Biofilms; Brushing; Candida albicans; Denture cleansers; Disinfectants; Oral hygiene